Custo de produção na terminação de novilhas em sistema de pastejo rotacionado e suplementação, Estado de São Paulo, Brasil - Pulici, Pedro H. da Silva; Oliveira, Suelen Moreira [UNESP]; Feitosa, Bianca Moraes; Proença, Ercio R. [UNESP]; Costa, Silvia Maria A. Lima [UNESP] (My University, 2016)
Brazil is home to the largest commercial cattle herd in the world and is a major exporter for the global animal protein markets. However still need to incorporate technology and intensify production systems to reap productivity gains and improvements of financial commitment. The work deals with the case study of a property (State of São Paulo, Brazil) specializes in fattening heifers for slaughter; calculated that the system production costs and profitability indicators. The activity showed to be satisfactory, the obtained profitability index shows that the system is possible as part of alternative production strategies for farmers.
Production cost in heifers grazing in termination system rotated and supplement, State of São Paulo, Brazil
Keywords: Cutting heifers; Production costs; Rotational grazing